Tranexamic Acid for Preventing Postpartum Blood Loss After Cesarean Delivery: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 5 (May 2016) - Simonazzi, Giuliana; Bisulli, Maria; Saccone, Gabriele; Moro, Elisa; Marshall, Ariela; Berghella, Vincenzo
Abstract : Abstracted from Acta Obstet Gynecol Scand 2016;95:28–37 The World Health Organization defines postpartum hemorrhage (PPH) as "blood loss from the birth canal in excess of 500 mL during the first 24 hours after delivery, " although currently there is a debate about what definition to use. Postpartum hemorrhage is responsible for approximately 25% of maternal deaths worldwide, and 12% of survivors will have severe anemia.